Invasive pneumococcal disease in Canada 2010–2017: The role of current and next-generation higher-valent pneumococcal conjugate vaccines. Issue 22 (21st May 2021) - Dion, Stephane B.; Major, Maria; Gabriela Grajales, Ana; Nepal, Rajeev M.; Cane, Alejandro; Gessner, Bradford; Vojicic, Jelena; Suaya, Jose A.
Highlights: The Canadian pediatric PCV13 programs reduced PCV13-serotype IPD cases in all ages. Decreases in PCV13-serotype IPD cases have plateaued since 2014. Decreases were most prominent in children aged <5 years compared with other ages. Further reductions may require increased PCV13 uptake in children and adults. Next-generation PCVs may help further reduce pneumococcal disease in Canada. Abstract: Background: In 2010–2011, the 13-valent pneumococcal conjugate vaccine (PCV13) replaced the 7- or 10-valent vaccine (PCV7 and PCV10, respectively) in pediatric immunization programs across Canada. For adults aged ≥65 years, the 23-valent pneumococcal polysaccharide vaccine (PPSV23) has been publicly funded for several decades; PCV13 funding was not recommended in this population, partly due to expected ongoing vaccine-serotype disease decline stemming from herd effects of the pediatric program. Higher-valent PCVs (ie, 15- and 20-valent PCVs [PCV15 and PCV20, respectively]) currently in development may become available in Canada in the coming years. Methods: Using the National Microbiology Laboratory surveillance reports, annual case counts and serotype distribution of invasive pneumococcal disease (IPD) from 2010 to 2017 in Canada were examined to assess the impact of existing programs on PCV13-serotype IPD and determine the proportion of IPD that can potentially be prevented by current and forthcoming higher-valent PCVs. Results: The percentages of PCV13-serotype IPD decreased from 55% [1492/2708] in 2010 to 30% [902/3006] in 2017 in all age groups combined, including a decline from 67% [221/331] to 18% [40/219] in children aged <5 years and from 50% [487/967] to 23% [287/1238] in adults aged ≥65 years. Overall, IPD cases declined mainly before 2014 and have plateaued since then. In 2017, PCV15- and PCV20-serotypes (inclusive of PCV13 serotypes) accounted for 42% and 58% of IPD cases, respectively, in all ages. Conclusions: In Canada, publicly funded pediatric PCV13 use was associated with large declines in IPD due to vaccine serotypes. Substantial residual PCV13-serotype IPD proportions observed among all ages imply limits to indirect protection afforded by the pediatric PCV13 program at the current uptake level and suggest the adult PPSV23 program alone is insufficient. Higher-valent PCVs have the potential to address a substantial proportion of remaining IPD cases among all age groups.